Graphene Nanomesh As Highly Sensitive Chemiresistor Gas Sensor - Paul, Rajat Kanti; Badhulika, Sushmee; Saucedo, Nuvia M; Mulchandani, Ashok (Analytical chemistry (Washington), 2012)
Graphene is a one atom thick carbon allotrope with all surface atoms that has attracted significant attention as a promising material as the conduction channel of a field-effect transistor and chemical field-effect transistor sensors. However, the zero bandgap of semimetal graphene still limits its application for these devices. In this work, ethanol-chemical vapor deposition (CVD) of a grown p-type semiconducting large-area monolayer graphene film was patterned into a nanomesh by the combination of nanosphere lithography and reactive ion etching and evaluated as a field-effect transistor and chemiresistor gas sensors. The resulting neck-width of the synthesized nanomesh was about ∼20 nm and was comprised of the gap between polystyrene (PS) spheres that was formed during the reactive ion etching (RIE) process. The neck-width and the periodicities of the graphene nanomesh (GNM) could be easily controlled depending on the duration/power of the RIE and the size of the PS nanospheres. The fabricated GNM transistor device exhibited promising electronic properties featuring a high drive current and an I ON/I OFF ratio of about 6, significantly higher than its film counterpart. Similarly, when applied as a chemiresistor gas sensor at room temperature, the graphene nanomesh sensor showed excellent sensitivity toward NO2 and NH3, significantly higher than their film counterparts. The ethanol-based graphene nanomesh sensors exhibited sensitivities of about 4.32%/ppm in NO2 and 0.71%/ppm in NH3 with limits of detection of 15 and 160 ppb, respectively. Our demonstrated studies on controlling the neck width of the nanomesh would lead to further improvement of graphene-based transistors and sensors.